AB0425 The Lornet Study in Russian Federation: the Safety of Tocilizumab in the Treatment Moderate and Severe Rheumatoid Arthritis. (10th June 2014) - Panasyuk, E.; Nasonov, E.
Abstract : Objectives: To evaluate interleukin 6 (IL-6) receptor inhibition with Tocilizumab (TCZ) in patient with moderate and severe RA in Russian Federation. Safety-related outcomes were analysed. Methods: A multicentre open-label phase IV study (LORNET: L ocal O pen-label multicentre study qualite of life patients with moderate and severe R A having iN adE quaT ely responded to DMARDs) was performed. A total 201 adult patients with active RA (DAS28>3, 2) who had to be naïve to biologics were enrolled in the study. Patients remained on stable doses of DMARDs and recieved TCZ 8 mg/kg every 4 weeks for 24 weeks. Results: Overall AE rates were 129, 99/100PY (per 100 patient-years). Serious AE were reported in 14, 5% of patients (19, 31/PY). 3 patients (1, 5%) withdrew from the treatment because AE. The most common AE leading to treatment withdrawal were anaphylaxis event (n=1), pneumonia (n=1), ALT/AST elevations (n=1). Infections, laboratory abnormalities (33, 46/PY and 39, 9/PY, respectively) were the most common AEs: upper respiratory tract infection (n=17), herpes labialis (n=3), infection of foot (n=2), onychomycosis (n=1), acute urinary tract infection (n=1), postinjectional abscess (n=1). One patient had cervical myelopathy. Shifts in ALT/AST up to 1-3 ULN occurred in 7, 5% of patients, had shifts to greater 3-5 ULN in 5, 0% and 2, 0% had shifts to greater than 5 ULN. The mean neutrophil count decreased from 5, 71x10 9 /l at baseline to 4, 46x10 9 /l at week 4 and 3, 77x10 9 /l at week 24. One patient had common toxity criteria grade 4 neutropenia <0, 5x10 9 /l. No serious infection were associated with neutrophil count. No death occurred during the study. Most of AE were mild or moderate and resolved by the end of the study. Conclusions: Tocilizumab is effective in treatment moderate and severe RA and generally good tolerated and safe with DMARDs combinations. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3590